ANALISIS KEBUTUHAN PARKIR PADA RUMAH SAKIT UMUM KELAS B DI KOTA SEMARANG - Hirtanto, Teguh; Ismiyati, Ismiyati; Wardani, Sri Prabandiyani Retno (Media Komunikasi dan Pengembangan Teknik Sipil, 2006)
Parking is one of the important elements of urban transportation, such, it has various long and short-term impacts on individuals, societies, and transportation systems. It affects to the transportation mode selection. People tend to drive private car when the representative parking area is available. This research is focused at the determination of the parameters that affect the use of parking area. The parameters are expected to be useful in estimating the parking area demand of the hospital class B in Semarang. There are six major parameters describing the parking slot, i.e.: accumulation, parking volume, total spaces available (capacity), parking turnover, peak time, duration of occupancy and occupancy. Three hospitals are selected as object of the study; there are RS Telogorejo, RS Elisabeth and RS dr Kariadi. The survey is carried out by direct investigation and questionnaire. Statistical analysis by using linear regression, logarithmic, quadratic, and exponential, indicated that the amount of bed used has a very high correlation with the parking demand. The next highest correlation is observed between medical specialist and parking demand. The average duration in RS Telogorejo is 15 – 30 minutes, RS Elisabeth is 30 minutes – 2 hours, and RS dr Kariadi is 15 – 30 minutes for car. For motorcycle, the average duration in RS Telogorejo is 30 minutes – 1 hour, RS Elisabeth is 30 minutes – 2 hours, and RS dr Kariadi is above 4 hours. From the study, it was found that the ratio between parking demand for vehicle and the number of bed being used is 0.89, meanwhile the ratio between parking demand for motorcycle and the number of bed being used is 1.29. Other alternative of parking facility like special parking building area is recommended to be considered for the hospital with limited area. Keywords: parking, hospital